Properties of high strength concrete with reduced amount of Portland cement– a case study. Issue 1 (1st January 2021) - Y B, Raghavendra; Y, Ramalinga Reddy; Hossiney, Nabil; H T, Dinesh
Abstract: In the last 15 years Bangalore city has systematically modernized its concrete production process with the help of ready-mix concrete (RMC) facility. However, one of the present requirements of these facilities is to lower its carbon footprint by reducing consumption of Portland cement in the concrete production process. Further, the demand for high-strength concrete (HSC) has increased due to construction of high-rise buildings and other major infrastructure projects in the urban areas of the city. Therefore, this study presents the experimental test results of HSC mixes proportioned with reduced consumption of Portland cement. Four types of concrete mixes with 50% of Portland cement replaced by ground granulated blast furnace slag (GGBS) were considered. Additionally, two control mixes without GGBS replacement were also tested. Fresh, hardened, and durability properties of all the mixes were experimental determined and presented. The results showed that concrete mixes proportioned with 50% GGBS obtained a maximum 28-day compressive strength of 77 MPa. Further, all the mixes with GGBS exhibited superior durability properties when compared to control mixes. Thus, concrete mixes with 50% GGBS replaced for Portland cement are favourable for producing HSC at RMC facilities at Bangalore city.